Do the ISO 14001 Environmental Management Systems Influence Eco-innovation Performance? Evidences from the EU Context. - Brogi, Stefano; Menichini, Tamara (European Journal of Sustainable Development, 2019)
Eco-innovation has become a clear target of EU policy strategies. Consequently, detecting drivers of eco-innovation has become crucial to design effective eco-innovation policies. The paper focuses on the adoption of ISO 14001 standard, with the aim to investigate to what extent the ISO certification of Environmental Management Systems influences eco-innovation performance. A correlation analysis between data from European Eco-Innovation Scoreboard interactive tool (ECO-IS) reveals that, at EU country level, there is no a significant correlation between the number of ISO 14001 certified organizations and the level of some selected Eco-Innovation performance indicators. Both the number of companies that have developed innovations with environmental benefits and the number of patents in environmentally-related technologies are not significantly related to the number of companies with ISO 14001 certification. Similar results were obtained by considering only Eco-Innovation leaders, that is EU countries with above-average Eco-Innovation Index values. These empirical evidences arise some questions and policy suggestions that will be discussed. Keywords: Eco-innovation drivers; Environmental Management Systems; ISO 14001 certification; Eco-Innovation Scoreboard; Eco-Innovation Index.